Investigations of Black and Red Figure Pottery Shards and Local Clay, Excavated at Ainos (Enez-Turkey), by Multiple Analytical Techniques - AKYÜZ, SEVİM; Çelik, Sefa; Kurap, Gülnur; Özel, Ayşen E.; Başaran, Sait (Elsevier, 2023)
Mineralogical compositions as well as firing conditions of black and red figure pottery shards, belonging to 4th6th century BC, excavated at the archeological site Ainos (Enez-Turkey), were investigated using Fourier Transform Infrared (FT-IR), micro-Raman, and X-Ray Powder Diffraction (XRPD) techniques. Raw clay, obtained from a clay bed, that was unearthed during the archeological excavations at the same site, was also analyzed for comparison. To determine the firing temperature of the pottery shards, ceramic tablets were prepared from this raw clay sample (in three different firing temperatures: 650, 700 and 900 degrees C) and analyzed. The results allowed us to identify the mineral composition and to discuss the firing conditions. Chemometric analysis on the IR data was performed for revealing the distinct groups.
Keywords: Ancient Ceramics; Clays; FT-IR and Raman; Firing Temperature; XRPD